Flexible Graduate is Successful Graduate. Key Factors of Successful Job Interview, Results of a Comparative Analysis - Vendolska Iva; Kacerova Eliska (Journal of Competitiveness, 2016)
The conditions on the labour market have changed dramatically in the last twenty years and the importance of human resources has increased. A company has to find, keep, and educate those workers who are able to adapt quickly to changes in the market. Such a company is then able to innovate constantly, which ensures its long-term competitiveness. Moreover, after finishing their education young people experience problems when seeking suitable employment. University graduates face stronger competition from other graduates when seeking employment. This target risk group of university graduates in particular is included in the primary research, together with the other side of the labour market, employers. The importance of individual criteria that are pivotal for employers during job interviews was examined on the basis of an anonymous questionnaire. 18 criteria were assessed and compared on a scale from 1 to 5. The correlation between the rate of importance of the given criterion and the group of respondents was tested. It was discovered that the criterion employers consider the most important is the flexibility and adaptability of a job candidate. This criterion is followed by willingness to learn, loyalty, and self-reliance. Those considered least important were these criteria: a stay abroad, courses/certificates, and studying at a particular university. On the other hand, the students consider the most important criteria to be foreign language skills, followed by communication skills, and willingness to learn and an internship during their studies. The criteria that were seen as the most important were: self-confidence, experience of a stay abroad, and the particular university that the student graduated from. The most significant difference in the assessment of the criteria between the employers and students was identified as being an internship during one’s studies.